2014
DOI: 10.17705/1cais.03503
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining the Momentum: Archival Analysis of Enterprise Resource Planning Systems (2006–2012)

Abstract: The domain of Enterprise Resource Planning (ERP) systems is an enduring paradigm for Information Systems (IS) researchers. The Enterprise System paradigm provides a rich environment to test fundamental concepts like system adoption, system use and system success, while acknowledging changes derived through longer system lifecycles and multiple user cohorts. On the other hand, ERP systems are in the centre of new contemporary radical changes in technologies on cloud computing, mobile platforms and big data. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 235 publications
(330 reference statements)
0
22
0
1
Order By: Relevance
“…Hence, it is important to focus on the dynamics of ES requirements beyond the implementation stage by analyzing how different contextual factors and experiences with the ES intertwine and shape the evolution requirements (Jarke et al, 2011). Although previous research acknowledges the volatility and evolution of requirements over time (Markus and Tanis, 2000), the evolution of requirements throughout the ES life cycle scarcely represents the unit of analysis (Esteves and Bohorquez, 2007;Eden et al, 2014). Particularly, research provides little explanation of the mechanisms that shape the requirements evolution process beyond implementation of the ES (Pollock and Williams, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is important to focus on the dynamics of ES requirements beyond the implementation stage by analyzing how different contextual factors and experiences with the ES intertwine and shape the evolution requirements (Jarke et al, 2011). Although previous research acknowledges the volatility and evolution of requirements over time (Markus and Tanis, 2000), the evolution of requirements throughout the ES life cycle scarcely represents the unit of analysis (Esteves and Bohorquez, 2007;Eden et al, 2014). Particularly, research provides little explanation of the mechanisms that shape the requirements evolution process beyond implementation of the ES (Pollock and Williams, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It addresses recently identified research gaps regarding customization, project evaluation, effort estimation, impact of adoption, system maintenance, performing updates with enterprise apps, and potential reasons for system abandonment (Eden et al, 2014;Parthasarathy, 2012). This study contributes to the system dynamics field by providing a new way of thinking about the rework cycle, often considered to be the most important feature of system dynamics project models (Lyneis & Ford, 2007), in an ERP post-implementation environment.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, the study and resulting model help address research gaps regarding software engineering issues such as customization, project evaluation, and effort estimation (Parthasarathy, 2012). The use of system dynamics modeling from a post-implementation perspective further addressed research gaps recently identified by Eden et al (2014), such as impact of adoption, system maintenance, performing updates with enterprise apps, and potential reasons for system abandonment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current situation provides interesting opportunities and challenges for the region. The sector is set to grow further, with a new wave of small-and medium-sized companies adopting packaged enterprise systems (Eden, Sedera, & Tan, 2014). The region has a different business ownership structure to the Western world, with a predominance of large family-owned or single-owner businesses.…”
Section: Darshana Sedera-outsourcing Large Packaged Applicationsmentioning
confidence: 99%